Staphylococcus aureus with reduced vancomycin susceptibility among clinical isolates in Erbil City - Taha, Aza Bahadeen; Al-Salihi, Sabria M.Said (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Staphylococcus aureus (S. aureus) is responsible for a wide range of diseases and increased number of the strains that acquired resistance to antibiotics. The emergence of Vancomycin resistance of S. aureus has been a significant impact on human health. The distribution of Vancomycin minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) in S. aureus isolates, and compared antibiotic susceptibility to non-glycopeptideantibiotics in different Vancomycin MIC value groupswere assessed in this study.Methods: S. aureuswere isolated by standard method and subjected to MIC tested by broth microdilution method for Vancomycin and eight non-glycopeptideantibiotics, alsoVancomycin MBCs were determined.Results: Approximately 56% of S. aureus with a 0.5 µg/ml Vancomycin MIC were accounted, whereas 1.77% of S. aureushadan 8 µg/ml Vancomycin MIC. In other hand, most S. aureus had 1 and 2 µg/ml Vancomycin MBC.Conclusion: About half of the S. aureus isolates had 0.5 µg/ml of Vancomycin MIC. Relationship between Vancomycin MIC and resistance to non-glycopeptideantibiotics were observed, with increased Vancomycin MIC, the resistance to others antibiotics also elevated, and vice versa.